PENGEMBANGAN MEDIA PEMBELAJARAN KARTU PLANET UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PELAJARAN IPAS DI KELAS V SDN 68 KOTA TIMUR - Usman, Sri Rahayu; Abdullah, Gamar; Arifin, Irvin Novita; Panai, Abdul Haris; Arif, Rifda Mardian (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to develop PLANET card-based learning media that are valid, practical, and effective for use in Natural and Social Sciences (IPAS) classes to improve student learning outcomes, specifically on the topic of the solar system, in Grade V of elementary school. The research was conducted at SDN 68 Kota Timur using a Research and Development (R&D) approach, following the ADDIE model Analyze, Design, Develop, Implement, and Evaluate To assess the validity of the PLANET card media, expert validation was carried out. Based on evaluations by experts and users, the PLANET card media received an average score of 92 40, indicating that it is highly suitable for use by both teachers and students in elementary schools. For practicality testing, an observation sheet was used, and the teacher received a score of 95 out of a maximum of 100, indicating a 95 practicality rating, which falls within the